Diffusional kurtosis MRI of the lower leg: changes caused by passive muscle elongation and shortening. (8th April 2016) - Filli, Lukas; Kenkel, David; Wurnig, Moritz C.; Boss, Andreas
Abstract : Diffusional kurtosis MRI (DKI) quantifies the deviation of water diffusion from a Gaussian distribution. We investigated the influence of passive elongation and shortening of the lower leg muscles on the DKI parameters D (diffusion coefficient) and K (kurtosis). After approval by the local ethics committee, eight healthy volunteers (age, 29.1 ± 2.9 years) underwent MRI of the lower leg at 3 T. Diffusion‐weighted images were acquired with 10 different b values at three ankle positions (passive dorsiflexion 10°, neutral position 0°, passive plantar flexion 40°). Parametrical maps of D and K were obtained by voxel‐wise fitting of the signal intensities using a non‐linear Levenberg–Marquardt algorithm. D and K were measured in the tibialis anterior, medial and lateral gastrocnemius, and soleus muscles. In the neutral position, D and K values were in the range between 1.66–1.79 × 10 –3 mm 2 /s and 0.21–0.39, respectively. D and K increased with passive shortening, and decreased with passive elongation, which could also be illustrated on the parametrical maps. In dorsiflexion, D ( p < 0.01) and K ( p = 0.036) were higher in the tibialis anterior than in the medial gastrocnemius. In plantar flexion, the opposite was found for K ( p = 0.035). DKI parameters in the lower leg muscles are significantly influenced by the ankle joint position, indicating that the diffusion of water molecules in skeletal muscle deviates from a Gaussian distribution depending on muscle tonus. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Diffusional kurtosis MRI (DKI) has recently gained interest for the detailed characterization of tissue microstructure. We demonstrate that diffusional kurtosis ( K ) in the lower leg muscles is significantly influenced by the joint ankle position. This extends our knowledge about the physiological microstructural behavior of skeletal muscle, and may have implications for future research on muscle pathologies.